ATP-Gated Ionotropic P2X7 Receptor Controls Follicular T Helper Cell Numbers in Peyer’s Patches to Promote Host-Microbiota Mutualism - Proietti, Michele; Cornacchione, Vanessa; Rezzonico Jost, Tanja; Romagnani, Andrea; Faliti, Caterina Elisa; Perruzza, Lisa; Rigoni, Rosita; Radaelli, Enrico; Caprioli, Flavio; Preziuso, Silvia; Brannetti, Barbara; Thelen, Marcus; et al. (Immunity (Cambridge, Mass.), 2014)
Microbial colonization of the gut induces the development of gut-associated lymphoid tissue (GALT). The molecular mechanisms that regulate GALT function and result in gut-commensal homeostasis are poorly defined. T follicular helper (Tfh) cells in Peyer’s patches (PPs) promote high-affinity IgA responses. Here we found that the ATP-gated ionotropic P2X7 receptor controls Tfh cell numbers in PPs. Lack of P2X7 in Tfh cells enhanced germinal center reactions and high-affinity IgA secretion and binding to commensals. The ensuing depletion of mucosal bacteria resulted in reduced systemic translocation of microbial components, lowering B1 cell stimulation and serum IgM concentrations. Mice lacking P2X7 had increased susceptibility to polymicrobial sepsis, which was rescued by Tfh cell depletion or administration of purified IgM. Thus, regulation of Tfh cells by P2X7 activity is important for mucosal colonization, which in turn results in IgM serum concentrations necessary to protect the host from bacteremia. [Display omitted] •P2X7 receptor controls T-cell-dependent IgA response to preserve commensalism•Lack of P2X7 receptor results in commensal depletion and reduced serum IgM•Mice lacking P2X7 receptor have increased susceptibility to polymicrobial sepsis•Purinergic control of Tfh cell help to B cells is conserved in humans T follicular helper (Tfh) cells in Peyer’s patches promote high-affinity IgA responses, which ensure mucosal protection. Grassi and colleagues demonstrate that P2X7 receptor-mediated regulation of Tfh cells allows mucosal colonization and controlled translocation of microbial components that stimulate systemic IgM and protect the host from bacteremia.